ANTONIO CASO, UNIVERSITY EDUCATOR - Torres, Morelos (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
The article is the result of a research about the career of Antonio Caso as university educator, and it focuses on the period of the Mexican Revolution and the post-revolution. As a complementary way, it discusses some Master Caso´s contributions that he made during the 30’s of last century, particularly in the debate on socialist education and training of intellectuals. The work analyzes the main ideas and actions of the Mexican educator, directly related to educational and university functions.